Effects of semidry flour milling on the quality attributes of rice flour and rice noodles in China. (March 2015) - Tong, Li-Tao; Gao, Xiaoxu; Lin, Lizhong; Liu, Yejia; Zhong, Kui; Liu, Liya; Zhou, Xianrong; Wang, Li; Zhou, Sumei
Abstract: To investigate the effects of semidry-milling on the quality attributes of rice flour and rice noodles, the properties of rice flours and cooking properties of rice noodles prepared with wet-, dry- and semidry-milled rice flours were characterized. The level of starch damage of semidry-milled rice flour at 30% moisture was significantly decreased to the level of wet-milled rice flour ( P  < 0.05); the whiteness of dry-milled rice flour was decreased compared with wet-milled rice flour ( P  < 0.05), while that of semidry-milled rice flour was not; the wet- and semidry-milled rice flours showed similar morphology and water hydration properties; the dry milling method reduced significantly the hardness, chewiness, and resilience of rice noodles ( P  < 0.05) compared with wet-milling, but semidry-milling did not; the cooking qualities of rice noodles produced by semidry-milling were comparable to wet-milling. It indicated the semidry-milling at 30% moisture may provide the protective effects on the characteristics of rice flours, which could be used to produce similar qualities of rice noodles to the wet-milling. Highlights: Semidry-milling showed protective effects on characteristics of rice flour. The semi-dry milled rice exhibited good water hydration properties. The qualities of rice noodles comparable to those of the wet-milled rice noodles.